Efeito do armazenamento nas características microbiológicas e físico-químicas do açúcar mascavo - Perez, Carolina da Silva (2023)
Microbiological and physicochemical characteristics are determining factors for the quality of raw cane sugar. The objective of this study was to investigate the influence of storage on the microbiological and physicochemical characteristics of brown sugar. The brown sugar samples were of industrial origin and differed in terms of moisture content (%): A=1.69; B=1.96; C=2.00; D=4.13 and particle size, and were stored for 365 days and analyzed every three months. Microbiological parameters were analyzed according to their compliance with national and international regulations, and physicochemical attributes were analyzed using analysis of variance followed by mean test and principal component analysis (PCA). The evaluated microbiological and physicochemical parameters were respectively: total coliforms; Escherichia coli; mesophilic bacteria; molds and yeasts; moisture content; water activity (AW); pH; conductimetric ash content; reducing sugars; Pol; and colorimetric color. The values of total coliforms and Escherichia coli were in compliance with Brazilian legislation. Only one sample of molds and yeasts exceeded the limit proposed by the current national legislation of 102 CFU/g. There was growth of colonies of mesophilic bacteria in all samples, which at certain storage periods were unsatisfactory according to international regulations. During the 365-day storage, there was random variation in moisture content, a tendency of increased water activity in samples C and D, colorimetric color changes, and a slight increase in conductimetric ash content; pH values were lower compared to time zero; reducing sugar levels decreased; Pol levels showed low polarization. Therefore, it is possible to observe that storage influenced most of the microbiological and physicochemical characteristics. However, since there are no reference values for identity and quality standards for this type of sugar, it cannot be stated that the variations in the evaluated parameters compromise the quality of the product. Nonetheless, the efficiency of good manufacturing practices during agro industrial processing and the quality of the raw material are evident.